The Effect of Red Palm Oil Concentration towards Characteristics and Biodegradability of PLA-Starch Film - Siti Fatma Abd Karim; Nur Aliah Adilla Mohammad Asri; Rabiatul Adawiyah Abdol Aziz; Ummi Kalthum Ibrahim (Indonesian Journal of Chemistry, 2020)
Polylactic acid (PLA) is a biodegradable polymer that had been used as a substitute for conventional petroleum based plastics. Plasticizers were added into the solution of PLA and starch (PLA/S) to increase the flexibility and degradability of the produced film. PLA/S films need plasticizers that able to improve the degradation process. Red palm oil (RPO) were incorporated into PLA/S blends. The films were casted into petri dish via casting method. The films were characterized based on the color, thickness and chemical composition (Fourier-transform infrared spectroscopy). The performance of the films was analyzed based on tensile strength and biodegradation percentage. The films were yellowish in color with the addition of RPO. The FTIR shows that the increment of RPO concentration modified the intermolecular interaction between the PLA/S molecules. The tensile strength of PLA decreased with the addition of starch. The biodegradability test was done by using soil burial method where the samples were buried in peaty soil for 12 days. The films produced from these combinations resulted in a good biodegradable activity. The films with high concentration of RPO and presence of starch degraded 100% within 12 days. RPO can be used as the plasticizer with further improvement.